2006
DOI: 10.1345/aph.1g407
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity to Warfarin After Heart Valve Replacement

Abstract: Immediately after heart valve replacement, patients are more sensitive to warfarin and should receive a lower warfarin dose during the initial phase of oral anticoagulation treatment. This enhanced sensitivity decreases with time. Patients require frequent monitoring and are likely to need an increase in the warfarin dose to avoid insufficient anticoagulation during the early follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 12 publications
2
32
1
Order By: Relevance
“…For Meijer et al, the dose requirement of warfarin after 3 months of therapy was 26% higher compared to first week of therapy (Meijer et al, 2009 Results showed that warfarin requirements were in increasing trend during the first three months after heart valve replacement (both AVR and MVR) but this pattern was absent in patients with AF. The trend was consistent with previous studies (Meijer et al, 2009;Rahman et al, 2006). Several factors might contribute to the increasing trend of mean warfarin dose among patients with AVR and MVR.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For Meijer et al, the dose requirement of warfarin after 3 months of therapy was 26% higher compared to first week of therapy (Meijer et al, 2009 Results showed that warfarin requirements were in increasing trend during the first three months after heart valve replacement (both AVR and MVR) but this pattern was absent in patients with AF. The trend was consistent with previous studies (Meijer et al, 2009;Rahman et al, 2006). Several factors might contribute to the increasing trend of mean warfarin dose among patients with AVR and MVR.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, diet which was different between Asian and Western populations might also contributed to the difference in warfarin dose needed (Jonas and McLeod, 2009) The mean warfarin dose in AVR and MVR patients after 3 months of therapy was 38.3% and 18.1% higher than first week of therapy. The result was consistent with study done by Mesbah Rahman et al and Meijer et al In result reported by Mesbah Rahman et al, the dose requirement of warfarin after 3 months of therapy was 43% higher compared to first week of therapy (Rahman et al, 2006). For Meijer et al, the dose requirement of warfarin after 3 months of therapy was 26% higher compared to first week of therapy (Meijer et al, 2009 Results showed that warfarin requirements were in increasing trend during the first three months after heart valve replacement (both AVR and MVR) but this pattern was absent in patients with AF.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations